Conducting qualitative research on acute mental health inpatient wards: Lessons from the field - Isobel Johnston; Helen Morley; Gill Gilworth; Jessica Raphael; Paul Wilson; Dawn Edge; Katherine Berry (PLoS ONE, 2025)
Qualitative process evaluations incorporating ethnographic observations and semi-structured interviews are increasingly being used to supplement randomised control trials when designing and testing complex health interventions, including in mental health inpatient settings. Yet how these components are conducted is less discussed. In this paper we describe our approach to conducting ethnographic participant observations on acute mental health inpatient wards. We discuss how we mitigated, negotiated, and adapted our research to effectively and sensitively complete these elements. We demonstrate the significance of personal and team reflective practice in guiding the research and provide reflections from the researchers on our direct experience of completing observations. Throughout the paper we discuss how we familiarised ourselves to individual research sites, reflected on our roles on the ward, adapted qualitative research techniques for acute mental health settings and the significance of peer debriefing.